Adaptive input shaper for payload swing control of a 5-DOF tower crane with parameter uncertainties and obstacle avoidance - S. M. Fasih ur Rehman; Z. Mohamed; A. R. Husain; L. Ramli; M. A. Abbasi; W. Anjum; M. H. Shaheed (Elsevier, 2024)
Indexed by WOS/Scopus/ERA